Atg11 is required for initiation of glucose starvation-induced autophagy. Issue 12 (1st December 2020) - Yao, Weijing; Li, Yixing; Wu, Liming; Wu, Choufei; Zhang, Yi; Liu, Jing; He, Zhiyong; Wu, Xiaoyong; Lu, Chenjun; Wang, Liefeng; Zhong, Huiming; Hong, Zhi; et al.
ABSTRACT: How energy deprivation induces macroautophagy/autophagy is not fully understood. Here, we show that Atg11, a receptor protein for cargo recognition in selective autophagy, is required for the initiation of glucose starvation-induced autophagy. Upon glucose starvation, Atg11 facilitates the interaction between Snf1 and Atg1, thus is required for Snf1-dependent Atg1 activation. Phagophore assembly site (PAS) formation requires Atg11 via its control of the association of Atg17 with Atg29-Atg31. The binding of Atg11 with Atg9 is crucial for recruiting Atg9 vesicles to the PAS and, thus, glucose starvation-induced autophagy. We propose Atg11 as a key initiation factor controlling multiple key steps in energy deprivation-induced autophagy. Abbreviations: AMPK: AMP-activated protein kinase; Ams1: α-mannosidase; Ape1: aminopeptidase I; Cvt: cytoplasm-to-vacuole targeting; GAPDH: glyceraldehyde 3-phosphate dehydrogenase; GFP: green fluorescent protein; MBP: myelin basic protein; MMS: methanesulfonate; PAS: phagophore assembly site; PNBM: p-nitrobenzyl mesylate; SD-G: glucose starvation medium; SD-N: nitrogen starvation medium; ULK1, unc-51 like autophagy activating kinase 1; WT: wild type